INTERNATIONAL BROADCASTING OF GREAT BRITAIN IN A GEOPOLITICAL CONTEXT - Vitaliy Tereshchuk (Інтегровані комунікації, 2024)
The article analyses the role of international broadcasting as a foreign policy tool in Great Britain and its transformation in the context of geopolitical changes. The relevance of this vector of research is based on the fact that for all the years of its existence, British foreign broadcasting has played a significant role both in the global media landscape and in the media spaces of most macro-regions of the world — European, Arab, African, etc. In addition, the formation of an image of the British National Broadcaster (BBC) as the benchmark of high standards of journalistic practice is undeniable. The purpose of the article is to reveal the role of the international broadcasting of Great Britain as a foreign policy tool and the features of the transformation of its goals and objectives under the influence of geopolitical imperatives. In order to achieve this goal, the tasks of identifying the stages of formation and development of the British foreign broadcasting system and finding out the influence of the geopolitical context on the transformation of the goals and target audiences of this broadcasting were implemented. It was revealed that the BBC World Service in different periods of its existence practised different models of broadcasting, realizing their inherent goals — colonial broadcasting (maintaining the unity of the British Empire), counter-propaganda in the interwar period and the period of the Second World War (countering informational influence alienation of Nazi Germany and the USSR), propaganda during the Second World War (formation of favourable public opinion regarding the activities of the anti-Hitler coalition) and the Cold War (anti-communist propaganda), in the times of the bipolar and post-bipolar world — positioning itself as a "surrogate" media that provides truthful news in countries where access to independent sources of information is limited by political regimes. As for the target audience, after a short period of purely colonial broadcasting, the objects of which were only British expatriates, the BBC’s international broadcasting has expanded to the indigenous population of the British colonies, as well as to the population of other countries.